Internationalization of Glitnir 2003-2008. Entering Norway - Anna Guðmunda Andrésdóttir 1985- (2009)
The main purpose of the report is to analyze the internationalization of Glitnir Bank, a leading company in the financial sector in Iceland. The internationalization started in 2003 and ended in 2008. Over the past few years internationalization of companies has grown rapidly. For that there are many reasons, such as easier communication and lower barriers for international trade than before. The world is getting smaller and now internationalization is much less of a risk than it was before. An interview was conducted with Rósant Már Torfason, one of the drivers of Glitnir´s internationalization. The company took its first steps into internationalization in 1993 by opening a branch in Luxemburg. After that, the ball began to roll. They started to focus on the Scandinavian market, and after a lot of deliberation Norway became their first and only choice. Glitnir had already established good business relationships in Norway, mainly because of their specialization in servicing the fishing industry. Glitnir entered the Norwegian financial sector in 2004 when they acquired KredittBanken. KredittBanken was a small local bank on the west coast of Norway mainly servicing the fishing industry. Glitnir knew that if they were to succeed in Norway they had to focus on other things than just the fishing industry. KredittBanken was always supposedly just a springboard into other financial companies in Norway. In 2005 Glitnir acquired BnBank, which was a much bigger bank and had other emphases than KredittBanken. The thing that KredittBanken and BnBank had in common was that 90 percent of their income was from net interest. Glitnir´s goal in Norway was to be an outstanding financial company. Their future goal was to be a leading commercial bank where the income was not mainly built on net interest bust mostly of securities and counsel compensation. After the acquisition of BnBank Glitnir realized that they had a lot of work ahead of them by integrating these two companies. That was going to be their biggest challenge. In this ...